Assessment of Pleural Effusion and Small Pleural Drain Insertion by Resident Doctors in an Intensive Care Unit: An Observational Study. Issue 13 (September 2019) - Vetrugno, Luigi; Guadagnin, Giovanni M; Barbariol, Federico; D'Incà, Stefano; Delrio, Silvia; Orso, Daniele; Girometti, Rossano; Volpicelli, Giovanni; Bove, Tiziana
Small-bore pleural drainage device insertion has become a first-line therapy for the treatment of pleural effusions (PLEFF) in the intensive care unit; however, no data are available regarding the performance of resident doctors in the execution of this procedure. Our aim was to assess the prevalence of complications related to ultrasound-guided percutaneous small-bore pleural drain insertion by resident doctors. In this single-center observational study, the primary outcome was the occurrence of complications. Secondary outcomes studied were as follows: estimation of PLEFF size by ultrasound and postprocedure changes in PaO2 /FiO2 ratio. In all, 87 pleural drains were inserted in 88 attempts. Of these, 16 were positioned by the senior intensivist following a failed attempt by the resident, giving a total of 71 successful placements performed by residents. In 13 cases (14.8%), difficulties were encountered in advancing the catheter over the guidewire. In 16 cases (18.4%), the drain was positioned by a senior intensivist after a failed attempt by a resident. In 8 cases (9.2%), the final chest X-ray revealed a kink in the catheter. A pneumothorax was identified in 21.8% of cases with a mean size (±SD) of just 10 mm (±6; maximum size: 20 mm). The mean size of PLEFF was 57.4 mm (±19.9), corresponding to 1148 mL (±430) according to Balik's formula. Ultrasound-guided placement of a small-bore pleural drain by resident doctors is a safe procedure, although it is associated with a rather high incidence of irrelevant pneumothoraces.